Tinjauan Teoritis Tentang Pengembangan dan Pemberdayaan Masyarakat dalam Perspektif Pembangunan Berkelanjutan : Theoretical Review of Community Development and Empowerment from The Perspective of Sustainable Development - Chaerani, Nurul; Wulandari, Febriana (JURNAL HUTAN TROPIKA, 2025)
Community development and empowerment are two key concepts in social development that complement each other. Community development is understood as a systematic process that emphasizes improving social, economic, and institutional welfare through active community participation in planning and evaluating development. Meanwhile, community empowerment focuses more on strengthening capacity, independence, and the ability of communities to manage resources and make decisions that affect their lives. The integration of these two concepts is important for realizing inclusive and sustainable development. This study uses a literature review method with a descriptive qualitative approach. Data were obtained from books, scientific journals, and policy documents related to community development and empowerment, then analyzed through content analysis to identify relevant concepts, approaches, and best practices. The results of the study show that there are various approaches that can be used, including participatory, rights-based, social economy, and technology and innovation approaches. These four approaches have been proven to increase the effectiveness of development programs, particularly in the agriculture and forestry sectors. However, challenges such as limited resources, low participation, and policy inconsistencies remain obstacles that need to be overcome. This study emphasizes that community development and empowerment should not only be oriented towards improving economic welfare, but also include social and ecological sustainability. Therefore, development strategies based on participation, local wisdom, and innovation are key to strengthening community independence while preserving the sustainability of natural resources